2010
DOI: 10.1007/s00404-010-1357-9
|View full text |Cite
|
Sign up to set email alerts
|

Uterine rupture in pregnancy: a five-year study

Abstract: The leading cause of uterine rupture was found to be neglected and obstructed labor due to mismanagement by local untrained birth attendants. Timely recognition and referral to higher centers can reduce the maternal and fetal morbidity and mortality due to uterine rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
0
23
1
Order By: Relevance
“…This is similar to a Indian study done by Gupta A (0.17%). 6 However study by Sahu L have higher incidence (0.29%). 1 In developing countries like Nigeria and Pakistan, kathmandu the incidence is 0.83%, 1.6% and 0.09% respectively.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This is similar to a Indian study done by Gupta A (0.17%). 6 However study by Sahu L have higher incidence (0.29%). 1 In developing countries like Nigeria and Pakistan, kathmandu the incidence is 0.83%, 1.6% and 0.09% respectively.…”
Section: Discussionmentioning
confidence: 89%
“…10 Anjali et al reported 70.17% cases in which uterine rent repair was done, 24.56% had subtotal, and 5.26% had total abdominal hysterectomy. 6 Turgut A et al had 34.4% cases with scar repair and total abdominal hysterectomy each, subtotal hysterectomy in his study was done in 31.1%. 15 Maternal mortality occurred in five cases (8.77%) which was more (3/5) in scarred uterus as compare to unscar one (2/5).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Its incidence has gradually declined over the years, in our study it was 1 in 924 deliveries (0.11) which is comparable to an Indian study done by Gupta A (0.17%). 2 The majority ruptures were in 21-30 years age group (76.53%) and 19.12% rupture occurred in 31-40 years age (Table 1). Out of 46 cases of uterine rupture, 39 i.e.…”
Section: Discussionmentioning
confidence: 91%
“…The prognosis in cases of neurological deficit after neuraxial blockade depends on whether there is axonotmesis (disruption of the myelin sheath, resulting in degeneration of the axon distal to the injury site) when recovery may take years, or only neuropraxia where recovery may be expected within three months; electromyography may be useful when formulating a prognosis. 2 Reassuringly, the 3rd National Audit Project highlighted that the incidence of serious complications after central neuraxial blockade in obstetric patients appears to be very low. 3 Shoulder-tip pain as an indicator of uterine rupture with a functioning epidural Uterine rupture in pregnancy is a rare and potentially catastrophic complication.…”
mentioning
confidence: 98%